Níveis de cortisol em recém-nascidos pré-termo : uma revisão sistemática e meta-análise - Silva, Juliana Fernandes da (2022)
Background: preterm birth is considered the main cause of death in children in the first 5 years of life, in addition to increasing the risks for global changes such as language disorders, motor skills, learning and neuropsychomotor delay in the child. It is estimated that nearly 30 million babies are born prematurely and require some intervention to survive. In the literature, no instrument is considered a “gold standard” in the assessment and management of neonatal pain, and some studies describe that exposure of the newborn to prolonged pain increases the levels of circulating cortisol in the body, modifying its brain organization and altering its function. pain perception. Methods: this systematic review and meta-analysis was developed following PRISMA standards (Preferred Reporting Items for Systematic Review and Meta-Analyses), and PICO eligibility criteria. The literature search took place in October 2020 and was updated in December 2021, in the databases MEDLINE (via Pubmed), EMBASE, CINAHL, PsycINFO. Registration was carried out on the PROSPERO platform (International Prospective Register of Systematic Reviews), under the number: Results and Conclusion: 22 studies constituted the systematic review and 20 the meta-analysis. Several studies identified alterations such as decrease/increase in cortisol levels, resulting in different directionality of effect sizes, corresponding to the absence of a significant result in the general analysis of meta-analysis. In the multivariate meta-regression session, there was no significant effect of potential moderators: weeks of gestation, birth weight, age range when cortisol assessment was performed, collection shift, and stressful/painful procedure. cowever, the moderator birth weight was significantly associated with variability of estimates, and an analysis restricted to studies with preterm infants with birth weight less than 1000g indicated an increase in cortisol in relation to the term group. Our results do not indicate a unique pattern of alteration in the production and release of cortisol in preterm newborns, however those with extremely low birth weight present a possible increase in cortisol levels.